Multimodal image registration for potential diagnosis and monitoring of morphoea using a hybrid NGC method - Izhar, L.I. (Institute of Electrical and Electronics Engineers Inc., 2017)
In medicine, thermal imaging diagnostic tool is increasingly employed thanks to its low cost, non-harmful and non-invasive nature. However, a thermogram can be quite ambiguous due to its low spatial resolution. This ambiguity can be reduced by incorporating information or data from different imaging sensors. This paper is an extension of a modified Normalized Gradient Correlation (NGC) employed in the initial phase of this study for multimodal image registration to assist in diagnosis and monitoring of linear morphoea. The proposed method is an improved, hybrid version of the modified NGC that incorporates an iterative based normalized cross-correlation coefficient (NCC) method for retrieval of translational differences based on the spatial domain in the initial method. The hybrid NGC method is found to reduce misregistration due to inaccurate retrieval of translational differences suffered by the initial NGC method in this multimodal image registration by up to 77.4 for over-detection error. © 2016 IEEE.